Wireless Energy Transfer with Three-Phase Magnetic Field System: Experimental Results - Luis, Romba (2018)
In this paper a three-phase magnetic field system is applied to the wireless power transfer system. The research is directed not only to the distribution of the magnetic field but to optimize the energy transfer efficiency, and to reduce the electromagnetic field influence to the surroundings. The development of the future intelligent transportation system depends on the electric mobility, namely, the individual or the public electric vehicles. It is crucial to achieve progress in the batteries and the battery charging, especially through a wireless power transfer technology. The study of the magnetic field is important in this technology. The energy transfer efficiency depends of the alignment, the size of the coils, the spatial orientation of the magnetic field, the detachment and the tilt between the windings.